Fibroblast growth factor 23 as a risk factor for cardiovascular events and mortality in patients in the EVOLVE trial. Issue 1 (5th October 2020) - Block, Geoffrey A.; Chertow, Glenn M.; Cooper, Kerry; Xing, Shan; Fouqueray, Bruno; Halperin, Marc; Danese, Mark D.
Abstract: Introduction: High mortality rates in patients with chronic kidney disease‐mineral and bone disorder (CKD‐MBD) receiving maintenance hemodialysis are largely due to cardiovascular (CV) events. Methods: We evaluated associations between MBD parameters, fibroblast growth factor 23 (FGF23) concentrations, and clinically adjudicated CV events from the Evaluation of Cinacalcet Hydrochloride Therapy to Lower Cardiovascular Events (EVOLVE) trial. Patients enrolled in EVOLVE, who had not experienced any study endpoints between randomization and week 20 with evaluable baseline and week 20 values for key laboratory parameters (parathyroid hormone, calcium, phosphate, and FGF23), were assessed. We used adjusted Cox proportional hazards regression models to estimate relative risk of outcomes (primary composite, all‐cause mortality, and CV events) based on FGF23 and MBD parameters. Laboratory values were modeled with linear terms and using natural cubic splines with two degrees of freedom. Findings: For the primary endpoint, patients assessed (N = 2309) were followed up over a mean duration of 3.1 years, during which 1037 CV events (497 deaths, 540 nonfatal events) occurred. Adjusted models showed an association between FGF23 and the risk of CV events. Hazard ratio per log unit of FGF23 at week 20 was 1.09 [95% CI: 1.03–1.16], and the hazard ratio per log unit change in FGF23 from week 0 to week 20 was 1.09 [95% CI: 1.00–1.17]. Discussion: Our data highlight FGF23 as an independent CV risk factor and potential biomarker and therapeutic target for patients with CKD‐MBD receiving maintenance hemodialysis.